HUBUNGAN KARAKTERISTIK PASIEN DENGAN TOKSISITAS HEPATOLOGI AKIBAT PENGGUNAAN 6-MERKAPTOPURIN DALAM FASE PEMELIHARAAN PADA PASIEN PEDIATRI KANKER LEUKIMIA LIMFOBLASTIK AKUT DI RS KANKER DHARMAIS JAKARTA - Nazhipah Isnani; Dyah Aryani Perwitasari; Rizka Andalusia; Haridini Intan Mahdi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Mercaptopurine is a chemotherapy drug that used in the consolidation and maintenance phase in pediatric patients with acute lymphoblastic leukemia ( ALL). Mercaptopurine is supposed to have relationship with the occurrence of toxicity in hepatology. This study was aimed to determine the patient incidence , severity and management of toxicity and risk factors that affect the occurrence of hepatologic toxicity using of 6 - MP in the maintenance phase in pediatric patients with acute lymphoblastic leukemia in Dharmais Cancer Hospital Jakarta. This research was carried out by cross-sectional observational design with data was taken retrospectively and prospectively during the period from March to April 2014. The study subjects were patient who have been getting treatment of maintenace phase in Dharmais Cancer Hospital Jakarta from 2013 until March-April 2014. The Subjects who met the inclusion criteria were 23 patients of ALL received 6 - MP in the maintenance phase. Data was collected by looking at the medical records for getting of the patient's identity and data hepatology. The result showed that there was a correlation between patient characterision on hepatology toxicity, on SGOT age and weight with SGPT both of them has significant value, it was 0,036 (P<0,05)